Unravelling effects of grazing intensity on genetic diversity and fitness of desert vegetation - Pelliza, Yamila Ivón (2020)
Biodiversity conservation focuses on species and/or populations, but preserving genetic diversity and structure has received limited attention and even less maintaining species evolutionary potential over generations. Genetic diversity is an essential component of biodiversity enabling species’ persistence, particularly under disturbances. Via sexual reproduction genetic diversity is transmitted across generations and greater outcrossing in parental populations will lead to greater genetic diversity in their offspring. Grazing by exotic large herbivores is one of the main disturbances driving biodiversity loss threatening rangelands sustainability worldwide. We investigated grazing effects on fitness and genetic diversity of parental and offspring cohorts of Prosopis alpataco from Patagonian Monte Desert. We collected fresh leaves and seeds from 10 independent rangelands with different herbivore density, forming a grazing gradient, and estimated genetic parameters from allele frequencies using isoenzymes. We recorded plant size, seed weight, seed set, seedling emergence and mortality as proxies of plant fitness. Applying regression models and path analysis (D-separation) approaches we observed that increasing grazing reduced seed set and seedling emergence, and significantly increased seedling mortality. Parental and offspring suffered from inbreeding. Moreover, we found genetic diversity loss throughout cohorts in all rangelands, however, this loss was relatively lower at intermediate grazing intensities. The introduction of large herbivores in unmanaged rangelands affected vegetation structure, jeopardizing their evolutionary potential and system sustainability. Therefore, natural revegetation may be compromised by aggravated genetic diversity losses along generations that might be deepened in drylands under forecasted climate change. This highlights the importance of evaluating and conserving genetic diversity.